Europa e Turchia: scontro di civiltà o incontro di democrazie? - Madonia, Thomas (SocietàMutamentoPolitica, 2010)
After the beginning of accession negotiations in 2005, debate over relations of European Union (EU) with Turkey has increasingly diverted toward cultural and religious issues. After arguing against the culturalist approach for framing the EU enlargement to Turkey, this article underlines the proactive role of EU in fostering democratic consolidation of Turkish society and political system. Furthermore, it is held that Turkey’s accession can bring benefits for European democracies as this step would make Europe to embrace cultural and religious diversities within its political and societal space.